Effect of Using Styrene Butadiene Rubber (SBR) on Physical, Mechanical, and Microstructure Properties of Recycled Coarse Aggregate Concrete Heating Grinding Method - Iram Syahrani; Ni Nyoman Kencanawati; Ngudiyono Ngudiyono; Miko Eniarti (Riviera Publishing, 2025)
Concrete is a widely used material in civil engineering projects. However, the excessive use of natural coarse aggregates can disrupt environmental balance and generate non-biodegradable concrete waste. An innovative solution to this problem is the use of recycled coarse aggregates. Nevertheless, recycled aggregates often cause microcracks and weak interface transition zones (ITZ) due to the presence of old mortar. This study aims to evaluate the effect of SBR additives on the physical, mechanical, and microscopic properties of concrete using recycled coarse aggregates processed through the heating-grinding (H-G) method, compared to conventional concrete. The research was conducted by varying the SBR content at 0%, 2.5%, 5%, and 10% by weight of mixing water. The results show that H-G concrete with 5% SBR content demonstrated the best performance, closely approaching the properties of normal concrete. Improvements were observed in compressive strength by 5.40%, split tensile strength by 0.59%, modulus of elasticity by 8.59%, and a reduction in water absorption by 5.02% compared to H-G concrete without SBR. Scanning Electron Microscope (SEM) analysis also indicated that the addition of SBR effectively minimized microcracks and improved the quality of the ITZ. In conclusion, the addition of 5% SBR to recycled aggregate concrete significantly enhances its physical and mechanical properties, providing a promising alternative for sustainable construction. The implication of this study is the potential broader application of recycled aggregates with SBR additives to reduce the environmental impact of concrete production.